Fetal and neonatal outcomes in early onset versus late onset pre-eclampsia-a comparative study - R., Vikram (International Journal of Contemporary Pediatrics, 2021)
Background: Pre-eclampsia is typed as two different entities: early-onset preeclampsia occurring at less than 34 weeks of gestation, and late-onset occurring at 34 or more weeks of gestation. The aim of this study is to compare the fetal and neonatal outcomes in early versus late onset preeclampsia. Methods: 208 patients diagnosed with pre-eclampsia in Shri Sathya Sai medical college and research institute over a period of three years (From January 2016 to January 2019) were retrospectively studied. Patients were classified as early onset and late onset pre-eclampsia based on the gestational age of onset. Data on fetal and neonatal outcomes were collected and analysed using Chi square and Fisher’s test and compared. Results: Early onset and late onset pre-eclampsia were 34.6% and 65.3%. The incidence of oligohydramnios, SGA, low APGAR at 5 minutes of birth were high in early onset type. 64.9% of early onset type required NICU admission whereas only 38.23% new born of mothers with late onset type required NICU admissions.10.8% of babies of patients with early onset type were still born. The incidence of NICU admissions, requirement of respiratory support, duration of NICU stay were significantly high in early onset type. Conclusions: Patients with early onset pre-eclampsia are found to have higher rates of specific fetal and neonatal morbidity when compared to the late onset type. Prudent and close scrutinizing and follow up and delaying delivery in stable and appropriately selected patients with pre-eclampsia would be advantageous for neonates.